Association between Yield Components of Sorghum (Sorghum Bicolor L. (Moench) Under Different Watering Intervals - Ibrahim, Elsadig B; Abdalla, Abdel Wahab H; Ibrahim, Elshiekh A; El Naim, Ahmed M (International Journal of Sustainable Agricultural Research, 2014)
A field experiment was conducted in the Sudan to study the extent of variability in grain yield and yield components of ten sorghum (Sorghum bicolor L. ( Moench) genotypesat three environments: Shendi (season, 2005/06), Shambat (season, 2005/06) and Shambat (season, 2006/07). A split- plot design with four replications was used. Two levels of water treatments were used, namely, irrigation every 10 days and every 21 days (drought stress condition). The main plots were allocated for water treatments and the sub plots for genotypes. Data on five characters, namely seed yield/plant, number of seeds/head, 1000-seed weight, seed yield (kg/ha) and harvest index, were collected. Genotypic and phenotypic correlations between different traits were determined. Grain yield exhibited strong positive phenotypic and genotypic correlations with its components. Significant positive associations were detected between performance of the evaluated genotypes under normal irrigation at Shendi and under water stress at Shamba tseasons (2005/06-2006/07) for number of seeds/head and 1000-seed weight. On the other hand, negative correlations were obtained between the performances at Shendi and Shambat (2006/07) under normal irrigation for seed yield/plant. Generally, these relations influenced the degree of associations between these traits and with the other traits in these environments.